Um ambiente virtual colaborativo para a educação de equipes cirúrgicas - Paiva, Paulo Vinícius de Farias (2014)
Virtual Reality (VR) can be understood as a human-computer interface which promotes a realistic experience for users when interacting with tridimensional virtual environments (VEs). Over the last years, medicine has benefited from the advent of VR, particularly in training and assessment context of several procedures. However, it is observed that many simulators take into account only the individual and technical aspects, while the abilities of interaction and assessment of the collaborative procedures are often disregarded, such as surgical procedures. This study was developed according to a well systematized methodology, including the following steps: a) Survey and analysis of VR systems focused on training and assessment in health sciences; b) Planning a CVE designed for training and assessment of students during surgical procedures. In this step, some professionals (surgeons, dentists, anesthesiologists) were contacted, some surgeries were observed and references guides were consulted in order to define all requirements of the simulator (target audience, goals, covered content, evaluation metrics, among others). After defining all requirements, a Collaborative Simulator for Surgical Education (SimCEC) was developed. The system is the result of studies on the use of VEs in education and the possibility of integration of decision methods as tools for users evaluation. The SimCEC has an evaluation system attached to it which is based on computed score and takes into consideration evaluation metrics, possible errors made as well as the weight of each simulated procedure. Lastly, it is intended that SimCEC can be used at specific times during the curricular content of higher education courses (at undergraduate level), as a tool to assist the teaching-learning process of future professionals. In this perspective, groups of students can train together in virtual space and contribute to the collaborative learning at a distance.